Characteristic of Wave and Magnet Textbooks (WMT) with RVGM-BASED to Train Student’s Critical Thinking Skills at Vocational High School - Diah Tri Wahyuni; I Ketut Mahardika; Supeno Supeno (Pancaran Pendidikan, 2017)
This research constitutes about the characteristic of WMT with RVGM-based to train Student’s critical thinking skills at vocational high school. The observational problem is how characteristic of WMT with RVGM-based to train Student’s critical thinking skills at vocational high school? This problem is enlightened deep two observational questions. First, what Binds WMT with RVGMbased application example comprising principle wave and magnet that train student’s critical thinking skills? Both of, how patterns to writing WMT with RVGM-based to vocational high school? This research constitutes development research binds textbooks, by use of mixed method exploratory model, which is gathered qualitatives data, then builds draft Physics Textbooks to becomes books validated ready. The subject in observational it is WMT with RVGMbased that can train Student’s critical thinking skills at vocational high school. Meanwhile, its respondent is student braze XI at vocational high school. Data collecting tech is observation, questionnaire, essay, and document. Observational data to be described qualitatively. Result observational to point out that WMT with RVGM-based application example comprising principle Wave and magnet that train Student’s critical thinking skills; and has given writing pattern, which has chapter heading thread, chapter sub title, the breakdown of material, trifling example, summary, ability quiz problem, and literature.